One-Pot Enantioselective Synthesis of Tryptophan Derivatives via Phase-Transfer Catalytic Alkylation of Glycine Using a Cinchona-Derived Catalyst - Todd, Robert; Huisman, Matthew; Uddin, Nazim; Oehm, Sarah; Hossain, M. Mahmun (Synlett, 2012)
Tryptophans are building blocks for many natural products. This paper describes the enantiospecific synthesis of ring-A substituted tryptophan derivatives from commercially available gramines using chiral phase-transfer conditions. This one-pot reaction avoids protecting/deprotecting the indolylic nitrogen of gramine by choosing a chemoselective quaternization reagent, 4-(trifluoro-methoxy)benzyl bromide, to produce an electrophilic salt intermediate, which is subsequently alkylated in good yield with high enantiomeric excess.
Keywords: asymmetric synthesis; one-pot; organocatalysis; phase transfer; tryptophan